Amoebic chronic appendicitis: a rare entity (Journal of Pathology of Nepal, 2016)
Rarely intestinal parasites can cause acute appendicitis. Amoebic appendicitis is rare and infection with Entamoeba Histolytica usually develops as an extension of caecal infection. I report a rare case of amoebic chronic appendicitis diagnosed on histopathology examination. It mimics the features of acute pappendicitis but may not always be responsible for acute appendicitis